2020
DOI: 10.1111/jerd.12599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytosphingosine on staining resistance and microhardness of tooth enamel

Abstract: Objective: To evaluate the protective effect of phytosphingosine (PHS) against staining on dental enamel. Materials and Methods: Ninety-six specimens of bovine teeth (6 mm × 6 mm × 2 mm) were cut, and initial color (Easyshade, VITA), microhardness (HMV-2, Shimadzu) and fluorescence (Matlabs software, Matworks) measurements were performed. Specimens were separated into four groups according to the treatments: Distilled water (control); Human saliva (HS); PHS; PHS + HS. Specimens (n = 6) were submitted to staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…with PHS, at different times of use, presented ΔE 00 values within the limit of perceptibility (0.80) established by the literature [30], different from the toothbrushing group, which showed values above this limit. In addition, all the tested groups, regardless of the period of use, revealed values below the limit of acceptability (1.80) [30].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…with PHS, at different times of use, presented ΔE 00 values within the limit of perceptibility (0.80) established by the literature [30], different from the toothbrushing group, which showed values above this limit. In addition, all the tested groups, regardless of the period of use, revealed values below the limit of acceptability (1.80) [30].…”
Section: Discussionmentioning
confidence: 63%
“…with PHS, at different times of use, presented ΔE 00 values within the limit of perceptibility (0.80) established by the literature [30], different from the toothbrushing group, which showed values above this limit. In addition, all the tested groups, regardless of the period of use, revealed values below the limit of acceptability (1.80) [30]. This fact is important, as it shows that the PHS was able to protect the dental enamel from the color change, and therefore, can be considered safe to be tested in future stages, such as in situ and in vivo assessments.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Seven studies assessed the effect of cigarette smoke/combusted tobacco particulate (CS extract) exposure on enamel or dentine (Alkhatib et al, 2005; Amorim et al, 2021; Dalrymple et al, 2018, 2021; Haiduc et al, 2020; Kobayashi et al, 2021; Ness et al, 1977). We pooled three studies with similar methodologies (Dalrymple et al, 2018, 2021; Haiduc et al, 2020) and found evidence that cigarette exposure caused a large change in color (increased staining), measured by E $\unicode{x02206}E$, of enamel or dentine compared with a nonexposure control (mean difference [MD]: 16.22; 95% confidence interval [CI]: 12.11, 20.32; I 2 : 96%; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…We pooled three studies with similar methodologies (Dalrymple et al, 2018, 2021; Haiduc et al, 2020) and found evidence that cigarette exposure caused a large change in color (increased staining), measured by E $\unicode{x02206}E$, of enamel or dentine compared with a nonexposure control (mean difference [MD]: 16.22; 95% confidence interval [CI]: 12.11, 20.32; I 2 : 96%; Figure 2). Within the studies not included in the meta‐analysis, Amorim et al (2021) showed that cigarette smoke caused a much smaller change in color (CIELab E00) if compared to the mean difference, this was still above the limit of perceptibility and acceptability. However, Kobayashi et al (2021) showed that when estimated, cigarette smoke caused twice the color change (CIELab E) $\unicode{x02206}E)$ of a nonexposure control.…”
Section: Resultsmentioning
confidence: 99%